1994
DOI: 10.1007/bf01306458
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial administrations of single or multiple source allogeneic cytotoxic T lymphocytes: chronic therapy for primary brain tumors

Abstract: Previous investigations by our group demonstrated the efficacy of single source allogeneic cytotoxic T lymphocytes (CTLs) given multiple times in reducing or curing tumor burden in the rat 9L gliosarcoma model. In this study, the lack of toxicity to normal brain when single source allogeneic CTLs were intracranially administered multiple times is documented. Additionally, the efficacy and lack of toxicity of allogeneic CTLs from multiple sources, each given once is documented. CTLs sensitized to Fischer antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…3 To overcome the problem of migration to malignant brain tumors, intracavitary infusion of LAK cells or allogeneic CTL cytotoxic T lymphocytes and IL-2 has been used in a number of clinical trials. 3,4,18,23,25,27,32,40,50 However, the results of these studies have been uniformly disappointing. Apparently, the mere presence of activated T cells in the tumor cavity is not sufficient to mediate tumor regression.…”
Section: Discussionmentioning
confidence: 96%
“…3 To overcome the problem of migration to malignant brain tumors, intracavitary infusion of LAK cells or allogeneic CTL cytotoxic T lymphocytes and IL-2 has been used in a number of clinical trials. 3,4,18,23,25,27,32,40,50 However, the results of these studies have been uniformly disappointing. Apparently, the mere presence of activated T cells in the tumor cavity is not sufficient to mediate tumor regression.…”
Section: Discussionmentioning
confidence: 96%
“…We reasoned that alloreactive CTL administered into the brain, an immunologically semiprivileged site, should be able to evade destruction by the host immune system long enough to give them time to actively destroy the tumor. Preclinical studies demonstrated the efficacy of this approach [42,43,45], and the development of human alloreactive CTL was refined in artificial capillary systems [51].…”
Section: Passive Adoptive Immunotherapiesmentioning
confidence: 99%
“…Our own laboratory has actively explored permutations of local adoptive immunotherapy for human malignant gliomas involving various effector cell types, including autologous lectin-stimulated and LAK cells [12,39], an allogeneic, irradiated cytotoxic T-cell line termed TALL-104 [40,41], and alloreactive CTL [42][43][44][45][46][47]. An allogeneic source for effectors holds the advantage of supply coming from an unrelated donor, rather than the immunosuppressed tumor-bearing individual, who may also be on immunosuppressive steroid treatment for control of brain edema.…”
Section: Passive Adoptive Immunotherapiesmentioning
confidence: 99%
“…[3] To overcome the problem of migration to malignant brain tumors, intracavitary infusion of LAK cells or allogeneic cytotoxic T lymphocytes and IL-2 has been used in a number of clinical trials. [3,4,18,23,25,27,32,40,50] However, the results of these studies have been uniformly disappointing. Apparently, the mere presence of activated T cells in the tumor cavity is not sufficient to mediate tumor regression.…”
Section: Discussionmentioning
confidence: 99%